FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIASAAN MAKAN PAGI PADA REMAJA PUTRI DI SEKOLAH MENENGAH PERTAMA (SMP) - Hermina, Hermina; Nofitasari, Ari; Anggorodi, Rina (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2012)
ABSTRACT Background: Having a breakfast is important for everyone, especially for school children, including teenage girls aged 13-15 years old to meet their energy requirements for their activities. Moreover, Having a breakfast has an effect for better studying performance. Objevtives: This study objective is to get the information about some factors that influence school teenage girls habitual breakfast. Methods: This Study is cross sectional study and was taking place in one of junior high schools in Depok town, West Java. Sample that had been recruited werw 217 school teenage girls, aged 13-15 years old. Data that had been collected in this study were habitual breakfast, knowledge, ideal body image, the availability of breakfast meal, school distance, having lunch money, habit of bringing meal to school, and parents education and income. Food recall data was collected by interviewing and other data was got by filling questioners in by samples. To analyze the relationship of some factors to habitual breakfast, chi square test and logistic regresi was used. Results: The percentage of teenage girl students having breakfast met their energy requirement is 58.5%, whereas who do not met the requirements is 41.5%. Teenage girls who have good nutrition knowledge are breakfast meal , mother education and teenage girls habitual breakfast (p<0.05). However, ideal body image, school distance, having lunch money, buying heavy meal at school, habit of bringing meal to school, father’s education, parents job and income, are not related to teenage girls habit of having breakfast (p>0.05). Conclusions: Some factors that influence habitual breakfast in teenage school girls are their nutrition knowledge, the availability of breakfast meal at home, their mother education. In addition the dominant factor that associated to that habit is mother education. Therefore, parents especially mothers should encourage their children to get used to eat breakfast. [Penel Gizi Makan 2009, 32(2): 94-100]. Key word: breakfast, habit, teenage girls, nutrition education, junior high school